Análisis de teoría de juegos en cadenas de suministros de dos niveles, productor-comprador, bajo esquema vendor managed inventory (vmi) (2014)
During the last decade, several models and strategies of coordination in supply chains have been developed, one of which is known as the Vendor Managed Inventory model (VMI). Despite the coordination efforts between the actors, sometimes it turns out that each one retains its restrictions and interests, which would preclude an integral implementation of the coordination strategy or agreement. A game theory based analysis approach is proposed for a supply chain comprising a producer (with a finite production rate) and a buyer (with known and constant demand), who have a VMI strategy, under two scenarios: Cooperative VMI and Non Cooperative VMI. A negotiation model where the one who gets more benefits can stimulate to the other agent who loses with agreement is proposed as well. A sensitivity analysis of the models has been performed in order to find the benefits to be gained in terms of savings in inventory costs and how these are distributed among the agents. The study results showed that under certain conditions and parameters, the VMI Cooperative model always favored the producer which did not happen with the buyer. However, the buyer may benefit from the VMI Cooperative model in its optimal point or by means of the economic incentive provided by the producer as a set in a bargaining model.